(3CWdS JGQjN GdOhdI GdYHGSjI (B/s - (3GdeZdhK, SGej YHO Gddg,s 1382 (3gLQj(B-s ((3GdQjGV(B:s (3ecJHI GdYHjcGf,s, 2012)
(3dbO LGA gPG GdCWdS aj SJI CHhGH QFjSI(B: (3JfGhd GdHGH GdChd bjGe GdOhdI, hJfGhd GdHGH GdKGfj(B: (3GdYUQ GdYHGSj GdChd, hJfGhd GdHGH GdKGdK(B: (3YUQ GdfahP GdJQcj, hJfGhd GdHGH GdQGHY(B: (3YUQ GdfahP GdHhjgj, hJfGhd GdHGH GdNGeS(B: (3YUQ GdfahP GdJQcj GdSdLhbj GdPj JNddg eLjA GdMedGJ GdUdjHjI Ydi GdeTQb GdESdGej, hSbhW GdOhdI GdYHGSjI Ydi CjOj GdeZhd SfI (B656 (3g`(B. (3HjfeG LGA GdHGH GdSGOS djJfGhd CHQR GdedGeM GdMVGQjI aj GdYUQ GdYHGSj(B. (3Ke CdMbfG gPg GdCHhGH HedGMb dEKHGJ GdeUGOQ hGdeQGLY, hagQS ddYfGhjf hGdCHhGH GdNGUI HgPG GdCWdS(B.s
Keywords: (3GdOhdI GdYHGSjIs -- (3JGQjNs -- (3NQGFWs